Numerical modelling of drop load tests. Issue 77 (October 2015) - Colombero, R.; Kontoe, S.; Foti, S.; Potts, D.M.
Abstract: Assessment of the attenuation of induced vibrations in the ground plays an important role in evaluating comfort and structural safety. Analytical and empirical wave attenuation relationships of increasing complexity and detail are presented in the paper, as well as a numerical model that accurately reproduces wave attenuation for a well-documented site, namely the one of the Tower of Pisa, Italy. A new source model is calibrated on near-field data and used as input for the dynamic coupled consolidation finite element analysis to achieve a satisfactory simulation. The accuracy of simpler analytical and empirical approaches is then comprehensively assessed through comparison with the validated numerical model and the field data obtained from geophones at various distances from the impact source. Highlights: A new equation to reproduce the drop-load test source signal is proposed. The induced waves attenuate with distance with a mixed power and exponential trend. The power trend is found dominant in many empirical vibration attenuation laws. Dynamic coupled consolidation FE simulations of drop load tests are performed. The numerical approach is reliable if site and test conditions are well understood.